THE ROLE OF ANCIENT PHILOSOPHY IN DEVELOPING CRITICAL THINKING IN STUDENTS (Eureka Journal of Humanities and Social Research, 2026)
The article analyzes the importance of ancient Greek philosophy - the teachings of Socrates, Plato and Aristotle - in the modern education system in developing critical thinking skills in students . The role of the Socratic method (elenchos and maieutics), Platonic dialectics and Aristotelian logic in modern pedagogy is highlighted. Today, in the age of artificial intelligence, educational models built on the basis of ancient methods (Socratic AI, Socratic chatbot) are also considered The ancient philosophical heritage and its role in the formation of critical thinking in the context of the digitalization of higher education in Uzbekistan are assessed
Keywords: Ancient philosophy, critical thinking, Socratic method, elenchos, maieutics, Plato's dialectics, Aristotle's logic, higher education, artificial intelligence, digital pedagogy.